O Craw Down na Recuperação de Empresas: entre o limite da atuação do poder judiciário e a efetividade da superação da crise - Cavalcanti, Arthur Miranda (2017)
The judicial reorganization of companies consists in a legal means for a company in economic and financial crisis to seek corporate reorganization and is provided in the Law 11101 of 2005, which regulates judicial recovery, extrajudicial recovery and bankruptcy of the company in crisis. According to legal provisions, through a procedure initiated directly by the debtor, the debtor must demonstrate to the creditors his viability to continue the business activity, providing the means of recovery that are skillful to obtain their approval. If the result of the General Meeting of Creditors is negative to the proposed recovery plan, the bankruptcy can be decreed. After this pronouncement of the creditors, the judiciary, according to the form adopted in the Brazilian legislation, is not able to replace, with greater freedom, the will of the majority of the creditors. Thus, the risk of judicial recovery does not succeed is imminent. However, there is an alternative to rejecting the will of creditors. This is the legal institution of Cram Down, a measure that gives the Judiciary greater powers to interfere and decide for the preservation of the company, even if the recovery plan has not been approved by the majority of the creditors, as provided for in the Recovery Act and Bankruptcies.Of foreign origin, Cram Down already finds defenders as an effective means of avoiding the breakdown of a viable company, but which is hostage to the individual interests of creditors. The study developed in the present work intends to identify if the decision made on the basis of the North American institute is possible within the legal reality of the Brazilian bankruptcy law and, in that case, to confirm if it is sufficent to produce results able to achieve the purpose of the recovery and, thus, able to fulfill the social function of the company. Doctrine and jurisprudence are the sources of study of this institute already adopted inforeign legislations, but still mitigated in our legal system.